Surface biofunctionalization of additive manufactured materials for implants with nano-thin polyelectrolyte multilayer coatings (Transactions on Additive Manufacturing Meets Medicine, 2024)
Titanium-based additive manufacturing of medical implants has attracted considerable attention over the past decade due to numerous advantages over standard manufacturing. Regarding the surface modification and biofunctionalization of additive manufactured titanium materials carried out by the application of coatings, however, very limited research has been reported so far. The interaction between the adherent tissues and the implant takes place at the interface between them, therefore the tissues response is strongly mediated and controlled by the surface properties of the implanted material. To the best of the authors' knowledge, this is the first study on the surface modification of additively manufactured titanium materials with ultrathin polyelectrolyte multilayer coatings. The application of these coating with a thickness of only a few nanometers proved to be able to impart chemical homogeneity to the surface and allowed targeted modification of the hydrophilicity of the additively manufactured titanium materials without changing their macro-topography and bulk properties. An important and first-of-its-kind finding of the present study, which is being reported for the first time, is the adhesion strength of polyelectrolyte coatings to the surface of additively manufactured titanium materials that were found to meet the requirements of the ISO regulations for coatings, applied to metal implants. The non-cytotoxicity and high adhesion strength classify the polyelectrolyte multilayer coatings as very promising for application as coatings of additively manufactured medical devices.
Keywords: Additive manufactured materials; Polymer coatings; Biofunctionalization; Surface properties; Biomaterials